Correlation between Geometrically Induced Oxygen Octahedral Tilts and Multiferroic Behaviors in BiFeO3 Films. (26th March 2018) - Lee, Sung Su; Kim, Young‐Min; Lee, Hyun‐Jae; Seo, Okkyun; Jeong, Hu Young; He, Qian; Borisevich, Albina Y.; Kang, Boyoun; Kwon, Owoong; Kang, Seunghun; Kim, Yunseok; Koo, Tae Yeong; et al.
Abstract: The equilibrium position of atoms in a unit cell is directly connected to crystal functionalities, e.g., ferroelectricity, ferromagnetism, and piezoelectricity. The artificial tuning of the energy landscape can involve repositioning atoms as well as manipulating the functionalities of perovskites (ABO3 ), which are good model systems to test this legacy. Mechanical energy from external sources accommodating various clamping substrates is utilized to perturb the energy state of perovskite materials fabricated on the substrates and consequently change their functionalities; however, this approach yields undesired complex behaviors of perovskite crystals, such as lattice distortion, displacement of B atoms, and/or tilting of oxygen octahedra. Owing to complimentary collaborations between experimental and theoretical studies, the effects of both lattice distortion and displacement of B atoms are well understood so far, which leaves us a simple question: Can we exclusively control the positions of oxygen atoms in perovskites for functionality manipulation? Here the artificial manipulation of oxygen octahedral tilt angles within multiferroic BiFeO3 thin films using strong oxygen octahedral coupling with bottom SrRuO3 layers is reported, which opens up new possibilities of oxygen octahedral engineering. Abstract : Multiferroic order parameters in BiFeO3 films are artificially manipulated using strong oxygen octahedral coupling with bottom SrRuO3 layers. The octahedral tilt direction and angles of the bottom SrRuO3 template layer form crucial parameters to determine the crystallographic structure, octahedral tilt angle, ferroelectricity, and ferromagnetism of the upper oxide films.